(3GdMhGTi GdCRgQjI aj GdebOeI GdLRQjIs - (3NGdO Hf YHO Gddg Hf CHj HcQ Hf eMeO GdLQLGhqj GdCRgQj, Rjf GdOjf, hcGf jYQa HGdhbGO , J (B905 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj CfRd Ydi YHOg GdcJGH s
(3BNQgG (B:s
(3ajSgd GdKGfjI hjLYdgG fbWI hhQT HYOeg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B9s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B275 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B292 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B188s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B- (3GdeZQH (B(1370 (3O(B) s
Keywords: (3GdMQha h GdChaGbs